A rare coincidence of different types of driver mutations among uterine leiomyomas (UL) - Holzmann, Carsten; Markowski, Dominique Nadine; Bartnitzke, Sabine; Koczan, Dirk; Helmke, Burkhard Maria; Bullerdiek, Jörn (Molecular cytogenetics, 2015)
Mutations of mediator subcomplex 12 (MED12) and of high mobility group protein AT-hook 2 (HMGA2) are driver mutations in uterine leiomyomas (UL) that have not been observed to coexist in one tumor and even rarely coexist in different UL tumors of one patient. Here we describe a patient who underwent hysterectomy because of multiple leiomyomas which were studied by cytogenetics, MED12 hotspot sequencing, and copy number variation arrays. Two of the UL tumors had different HMGA2 rearrangements not detected by G-banding. Two UL tumors had deletions of the long arm of chromosome 3, in one case associated with a MED12 mutation. Both deletions lead to the loss of MED12L showing strong similarity with MED12. It remains to be determined if this gene can play a role in leiomyomagenesis independent of MED12. In summary, the patient presented exhibits an unusual coincidence of different driver mutations among her leiomyomas.
Gesehen am 08.09.2020